THE IMPACTS OF INTERNATIONAL GUESTS' EXPERIENCE ON LOYALTY IN HOSTELS - Sarinya La-ong-in Thayarnsin, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Customer loyalty plays a crucial role in the success of hostels in the competitive accommodation business market. This study aims to evaluate the roles of the tourist experience, memory, and image by examining their influences on the process of creating customer loyalty towards the hostels. The study adopts a quantitative approach. This study also draws a comprehensive data set (N=445) using a convenience sampling approach. The sample was international guests who have experienced in hostels in Bangkok, Thailand. The study employed confirmatory factor analysis and structural equation modelling to achieve the objectives. Findings from the structural analysis indicate a good fit for the proposed model. The findings also reveal that guest experience has significant associations affecting memory which in turn influences loyalty. Subsequently, the guest experience has a positive effect on the image which in turn influences loyalty. Consequently, the guest experience has a significant influence on loyalty. Several implications for theory and practice are discussed in this study.